IMPLICATION OF ISLAMIC COUNSELING FOR KODAM I/BUKIT BARISAN SOLDIERS - Saiful Akhyar Lubis; Abdurrahman Abdurrahman; Syawal Fahmi (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
This study aims to determine the implications of Islamic counseling in mentoring mentors of Kodam I/Bukit Barisan. Data collection methods in this study used qualitative analysis with observation, interview, and documentation techniques. The results showed that the implications of Islamic counseling for Kodam I Bukit Barisan soldiers functioned as enlightenment for soldiers who have problems in life. At the same time Islamic counseling also plays a role in minimizing the occurrence of violations of work discipline and moral violations of soldiers when they are on duty, as well as when they are in the community. Thus it can be assumed that the role of Islamic counseling for Kodam I Bukit Barisan soldiers is very significant in supporting the smooth running of their duties.